2013
DOI: 10.1002/jor.22352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastin digestion on the quasi-static tensile response of medial collateral ligament

Abstract: Elastin is a structural protein that provides resilience to biological tissues. We examined the contributions of elastin to the quasi-static tensile response of porcine medial collateral ligament through targeted disruption of the elastin network with pancreatic elastase. Elastase concentration and treatment time were varied to determine a dose response. Whereas elastin content decreased with increasing elastase concentration and treatment time, the change in peak stress after cyclic loading reached a plateau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 31 publications
(62 reference statements)
11
87
2
1
Order By: Relevance
“…Porcine MCL was chosen as it is a readily available planar ligament that is large enough to allow isolation of multiple rectangular test specimens, and its native material properties are similar to human MCL [5, 11]. The tissue was thawed and the ligament was fine dissected to remove overlying fascia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine MCL was chosen as it is a readily available planar ligament that is large enough to allow isolation of multiple rectangular test specimens, and its native material properties are similar to human MCL [5, 11]. The tissue was thawed and the ligament was fine dissected to remove overlying fascia.…”
Section: Methodsmentioning
confidence: 99%
“…We recently examined the role of elastin in ligament mechanics via selective degradation with elastase [9] and found that elastin provided a disproportionately high contribution during uniaxial tensile deformation along the primary collagen axis. Although elastin constituted only 4% of the tissue dry weight, it supported up to 30% of tensile stress under uniaxial strain [5]. In addition, elastin is localized between and along collagen fibers in cruciate ligaments [10].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic screening studies have suggested that collagen Type VI may be an important component of the tendon ECM [64], being a pericellular matrix protein that plays a role in collagen fibrillogenesis [65]. Beyond the fibrillar collagens, elastin is a fibrillar glycoprotein contributing 1-2% of tendon dry mass that plays a role in recoil of the matrix after repetitive mechanical loading [66]. Binding the fibrillar matrix are numerous FACITs (fibril-associated collagens with interrupted triple helices) that regulate interactions between the fibrillar matrix and other ECM molecules.…”
Section: Tendon Core -Multiscale Structure and Functionmentioning
confidence: 99%
“…3A) [53]. While collagen is generally thought to be the main mechanical element in tendons, removal of non-collagenous molecules, such as elastin or glycosaminoglycans, reduces the whole tendon mechanical response, emphasizing their role in development, homeostasis, and load transfer [5456]. …”
Section: Case Study 1: the Extracellular Matrix In The Tendonmentioning
confidence: 99%